After the earth moved: Accounting and accountability for earthquake relief and recovery in early twentieth-century New Zealand. (November 2015) - Vosslamber, Rob
There has been little discussion of what archival accounting evidence can contribute to an understanding of a society's response to a natural disaster. This article focuses on two severe earthquakes which struck New Zealand in 1929 and 1931 and makes two main contributions to accounting history. First, by discussing evidence from archival sources, it contributes to the literature on accounting in a disaster. This provides a basis for future theory building and for future comparative research related to the response to more recent natural disasters such as the 2010–11 Canterbury earthquakes. Secondly, it questions the conclusions of recently published research concerning the role of central and local government in this and recent earthquakes.